Legal Consequences of The Absense of Informed Consent in Therapeutic Transactions - Sacharissa, Vicia (Jurnal Mulawarman Law Review, 2020)
A person's right to their own body is one of the human rights protected under the right to self-determination,1 and this protection also applies to patients seeking treatments. The process of giving information by the doctor, which is then followed with the consent to medical action by patient, is known as informed consent. In Indonesia, the protection of such right is contained in various laws and regulations. This is a descriptive legal research, with normative-judicial or library research method and qualitative data analysis. The discussion covers topics regarding therapeutic transaction as a form of agreement, the presence of informed consent in therapeutic transactions, and the consequence of the absence of informed consent from the perspective of civil law. It is also supplemented with case decision study on Case Decision No. 3203 K/Pdt/2017 which proves that the lack of informed consent is a legitimate ground for a lawsuit.